The Impact of the CoVid-19 Pandemic upon the Contracts in Progress. Special View upon the Unforeseeability in the Regulation of the Romanian Civil Code (Discourse of Law and Administration, 2021)
In the context of the deep economic changes generated by the SARS-CoV-2 pandemic, the debates regarding the institution of unforeseeability have returned. It is a fact that the measures ordered by the authorities to limit the spread of the pandemic affect the possibility of fulfilling contractual obligations, so that the contracting parties are put in a position to analyze the contractual mechanisms available to remedy the situation. The Romanian legal system considers the unforeseeability as an exception from the principle of the binding force of the contract, being expressly stated by the current Civil Code. It is applicable, as a rule, for the synallagmatic, onerous, commutative and with successive or continuous execution contracts. This exception may be invoked if the execution of the contract has become excessively onerous for one of the parties, because of the occurrence of certain events independent of the will of the parties and which caused an imbalance between their services, impossible to foresee at the time of concluding the act. Invoking the unforeseen allows the contract to be renegotiated. If the parties do not reach an agreement, at the request of one of them, the court may adjust or order the cessation of the contract. Starting from the fact that there are multiple situations in which the spread of the CoVid-19 has determined a contractual imbalance, which needs to be remedied, as well as the fact that practically there is still a confusion between the application of the unforeseeability and the situations in which the major force occurs as an exonerating cause of liability, the objective of the current article is to analyze the concept of unforeseeability and the legal regime applicable to it, by emphasizing the conditions which need to be met in order to be in the presence of this exception from the principle of the binding force of the contract.
Keywords: Romanian Civil Code; unforeseeability; the conditions of unforeseeability; the effects of unforeseeability; CoVid-19 pandemic; the limitation of the binding force of the contract